Chemical composition and antimicrobial activity of the essential oil from \(Magnolia balansae\) A. DC. growing in Vietnam - Hà, Chu Thị Thu; Huy Thai, Tran; Thi Hien, Nguyen; Ngoc Diep, Le; Thi Thu Thuy, Dinh (Academia Journal of Biology, 2022)
Essential oils of Magnolia balansae A. DC. growing wild in Son La (leaf, twig and fruit) and Phu Tho (fruit) provinces of Vietnam were obtained by hydrodistillation and were analyzed using GC/MS-FID. From 30 to 49 compounds were identified accounting for 66.1–80.0% of the oils. Spathulenol (33.9%, 20.7%, and 11.2%), and caryophyllene oxide (10.0%, 10.1%, and 9.3%) were the main components of leaf, twig and fruit oils of M. balansae, respectively, from Son La province. Linalool (13.8%) was also the main component of fruit oil. While, in the fruit oil of M. balansae from Phu Tho province, cis-β-elemene (10.4%) was the sole main component. The antimicrobial activity of the oils was tested against 3 microorganism strains using an agar disk diffusion method with inhibitory zone diameters ranging from 13.5 to 40 mm. IC50 and MIC of the M. balansae oils were determined using a microdilution broth susceptibility assay against 7 microorganism strains. Among them, Bacillus subtilis had the highest sensitivity with IC50 values (ranging from 57.0 to 82.0 µg/mL) and MIC value (512 µg/mL). This is the first study on the chemical composition of essential oils of M. balansae and their antimicrobial activity.